TRANSITIVITY AND MEANING CONSTRUCTION IN CHILD-PARENT SONG LYRICS ACROSS CULTURES - Hiace Vega Fernando Siahaan; Natal P Sitanggang; Tri Amanat; Erwin Kembaren; Rikki Nelson Lumban Gaol (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines transitivity processes in English and Indonesian parent–child-themed song lyrics using Halliday’s (2014) Systemic Functional Linguistics framework. By analyzing six transitivity process types—material, mental, verbal, relational, behavioral, and existential—the study explores how linguistic choices construct emotional relationships, social roles, and family values across different cultural contexts. The data consisted of twenty song lyrics collected from YouTube channels. Data were gathered through listening and note-taking techniques and analyzed using an interactive qualitative model involving identification, classification, and interpretation of transitivity processes. The findings reveal that material processes are the most dominant (33.4%), indicating that song narratives primarily rely on concrete actions to express emotions and interpersonal experiences. Mental processes (24.9%) and relational processes (22.4%) follow, contributing psychological and descriptive dimensions to the portrayal of parent–child relationships. Verbal, existential, and behavioral processes occur less frequently and serve complementary narrative functions. The predominance of material processes demonstrates that meaning construction in both English and Indonesian song lyrics is strongly grounded in physical actions and observable events. Common actions represented include giving, accompanying, caring for, and supporting, reflecting parental affection and responsibility. The findings suggest that, despite cultural differences, both groups of songs emphasize similar familial values through action-oriented representations. This study contributes to cross-cultural discourse research by demonstrating how song lyrics function as a medium for conveying emotional meaning and intergenerational social relationships across cultural communities.